2007
DOI: 10.1037/0021-843x.116.3.554
|View full text |Cite
|
Sign up to set email alerts
|

Delinquent peer affiliation and conduct problems: A twin study.

Abstract: Many putative environmental risks correlate with individuals' genotypes. The association between delinquent peer affiliation and conduct problems may occur because of shared genetic liability. Five hundred fifty three monozygotic and 558 dizygotic twin pairs, aged 11 to 18 years, were assessed for delinquent peer affiliation and conduct problems. The authors investigated whether genes contribute to both delinquent peer affiliation and the correlation between delinquent peer affiliations and conduct problems. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
57
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 62 publications
12
57
1
Order By: Relevance
“…Overall, the results for effects of delinquent friends reflect a pattern that individuals who have friends that are increasingly delinquent through adolescence are also more likely to follow a pattern of increased delinquency. This is consistent with a number of past studies (Button et al 2007;Miller et al 2009;Rebellon 2006). As mentioned above, the finding that peer behavior influences delinquency is not surprising; the more interesting question lies in disentangling this effect.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, the results for effects of delinquent friends reflect a pattern that individuals who have friends that are increasingly delinquent through adolescence are also more likely to follow a pattern of increased delinquency. This is consistent with a number of past studies (Button et al 2007;Miller et al 2009;Rebellon 2006). As mentioned above, the finding that peer behavior influences delinquency is not surprising; the more interesting question lies in disentangling this effect.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, evidence from genetically-informed studies uniformly suggests that genetic influences on aggressive and delinquent behavior are indeed amplified when adolescents affiliate with deviant peers. These findings, which reflect what is termed a gene  environment interaction (GÂE), are observed with adolescent samples even when controlling for rGE (Button et al, 2007). They are also observed with children.…”
Section: Discussionsupporting
confidence: 58%
“…A consequence of being rejected by ''normally'' developing children might be affiliating with deviant peers, which then provides new opportunities to engage in antisocial activities. Twin studies have revealed that the contribution of genetic factors to aggression increases with higher levels of deviant behavior in the peer group of a child or adolescent (Brendgen et al 2008a;Button et al 2007). Moreover, aggressive friends enhanced the likelihood of antisocial behavior especially in children with a high genetic risk (van Lier et al 2007).…”
Section: Behavioral Genetic Studies Of G 3 Ementioning
confidence: 98%